2007
DOI: 10.1128/jvi.02458-06
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and Genetic Evolution of Swine Influenza A (H3N2) Viruses in Europe

Abstract: In the early 1970s, a human influenza A/Port Chalmers/1/73 (H3N2)-like virus colonized the European swine population. Analyses of swine influenza A (H3N2) viruses isolated in The Netherlands and Belgium revealed that in the early 1990s, antigenic drift had occurred, away from A/Port Chalmers/1/73, the strain commonly used in influenza vaccines for pigs. Here we show that Italian swine influenza A (H3N2) viruses displayed antigenic and genetic changes similar to those observed in Northern European viruses in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 21 publications
5
121
1
1
Order By: Relevance
“…The HA of these swine viruses descended from the 1918 pandemic influenza virus but, in contrast to the human lineage, did not undergo extensive antigenic drift, as was reported for A(H3N2) swine viruses (19). Structural analyses suggested high antigenic similarity between the A(H1N1)pdm09 virus and A(H1N1) viruses that circulated in the first decades after the 1918 pandemic (20,21).…”
mentioning
confidence: 84%
“…The HA of these swine viruses descended from the 1918 pandemic influenza virus but, in contrast to the human lineage, did not undergo extensive antigenic drift, as was reported for A(H3N2) swine viruses (19). Structural analyses suggested high antigenic similarity between the A(H1N1)pdm09 virus and A(H1N1) viruses that circulated in the first decades after the 1918 pandemic (20,21).…”
mentioning
confidence: 84%
“…A characteristic that distinguishes swine from other mammalian IAV hosts, including humans, horses, canines, and seals, is the number of IAVs from a different host (in this case, mainly humans) that have successfully adapted to onward transmission in swine (10)(11)(12)(13)(14)(15). The global frequency of human-to-swine trans-mission of the 2009 H1N1 pandemic virus (pH1N1) in recent years reinforces the importance of "reverse zoonosis" of human viruses as a major source of IAV diversity in swine (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…De Jong et al showed in 2007 that swine influenza viruses seem to have a slower antigenic evolution than their human counterparts, despite similar genetic evolution rates of their hemagglutinin protein genes. 16,17 This finding can be attributed to the nature of the host populations, one long-lived with multiple influenza exposures, the other shortlived with few exposures. Therefore, although the number of mutations generated is similar, the viruses in humans are under selective pressure to fix mutations that result in a favorable antigenic change.…”
Section: Antigenic Variationmentioning
confidence: 98%